Estimation of flash flood hazard in the Pidima-Arfara area (Messinia, SW Greece), based on the study of instantaneous unitary hydrographs, longitudinal profilesand stream power - Sambaziotis, E.; Fountoulis, I. (Bulletin of the Geological Society of Greece, 2007)
In this paper it is an effort to combine different methodologies in order to locate the sensitive sites in flash flood phenomena in a relatively small catchment located north of Kalamata (Messinia SW Péloponnèse, Greece). Based on digitised topographic map (scale 1/5.000) the longitudinal, gradient and stream power profiles of the watercourses were constructed and the results (possibly sensitive to flash floods sites) were compared to ones that came from applying hydrological simulation, hydrographs as well as Instantaneous Unitary Hydrographs. The comparison showed that the results were in good agreement.